2020
DOI: 10.21203/rs.2.20323/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sociodemographic factors associated with request for labor epidural analgesia in a tertiary obstetric hospital in Vietnam

Abstract: Background Labor epidural pain relief remains underutilized in developing countries and may serve as a marker of health care access disparity. Here we examine the sociodemographic factors associated with the utilization of labor epidural analgesia at a large obstetrics and gynecology hospital in Vietnam.Methods This was a cross-sectional study of women who underwent vaginal delivery in September 2018 at the Hanoi Obstetrics and Gynecology Hospital. Utilization of epidural analgesia during labor was determined.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
2
3
1
1
Order By: Relevance
“…Our study further noted that educated women dominated the demand for epidural analgesia because they are better informed about the trending events especially as it concerns their reproductive health. This submission therefore suggests that their knowledge of epidural technique for labor pains could have contributed to the level of demand observed which corroborated the reports of other authors [10][11][12][13].Additionally, parturients who utilized labour epidurals were significantly older than 30 years of age (p=0.002), multiparous (p=0.001), and were higher income earners (p=<0.001) This was in consistent with previous Vietnam Study [1]. .Apart from the knowledge of labor epidural analgesia, a few other concerns had continued to challenge its wide use in our setting which included the effect of epidural analgesia on the outcome of labor in terms of progress of labor, mode of delivery and backache.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study further noted that educated women dominated the demand for epidural analgesia because they are better informed about the trending events especially as it concerns their reproductive health. This submission therefore suggests that their knowledge of epidural technique for labor pains could have contributed to the level of demand observed which corroborated the reports of other authors [10][11][12][13].Additionally, parturients who utilized labour epidurals were significantly older than 30 years of age (p=0.002), multiparous (p=0.001), and were higher income earners (p=<0.001) This was in consistent with previous Vietnam Study [1]. .Apart from the knowledge of labor epidural analgesia, a few other concerns had continued to challenge its wide use in our setting which included the effect of epidural analgesia on the outcome of labor in terms of progress of labor, mode of delivery and backache.…”
Section: Discussionsupporting
confidence: 91%
“…Maternal childbirth care is one of the main indices of development of any nation and this could be gauged best by the type of labor analgesia she receives during pregnancy and childbirth [1][2][3]. Child birth unarguably is a desirable event but has been described as the most painful, emotionally and physically distressing experience affecting the mother, fetal wellbeing as well as progress of labor [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we studied the factors that could influence participants' desire to receive EPA during labor and found that women with higher levels of education were more likely to request EPA during delivery, which was consistent with a previous study conducted in Vietnam [12]. Similarly, a study carried out in the United States revealed a significant association between the level of education and epidural request [13].…”
Section: Discussionsupporting
confidence: 87%
“…Factors such as employment were associated with the request of the epidural analgesia in a study conducted in Riyadh [8], which was inconsistent with our results. A couple of studies found that expectant mothers with health insurance were more likely to request EPA during labor [12,14]. In contrast, in our study, financial factors did not contribute to decision-making because our study setting was in a government hospital where free health care is provided.…”
Section: Discussioncontrasting
confidence: 59%
“…Em 1981 foi criada a técnica de bloqueio combinado (11), a qual vem ganhando crescente popularidade durante os últimos anos. Cerca de 75-80% das parturientes no Reino Unido, 75% das mulheres francesas e 73% das americanas recebem bloqueio de neuroeixo para alívio da dor (12)(13)(14), embora taxas mais baixas possam ser encontradas a depender do serviço de saúde, paridade prévia, grau de instrução da paciente ou até mesmo devido a diferenças culturais entre os países (15,16). No Brasil, apenas 16% das pacientes atendidas no serviço público e cerca de 50% atendidas no serviço privado recebem analgesia neuroaxial (17).…”
Section: -Introduçãounclassified